2020
DOI: 10.1055/a-1344-4271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Isolated Lupus Anticoagulant Positivity in Patients with Thrombotic Antiphospholipid Syndrome

Abstract: Background: Patients positive for three types of antiphospholipid antibodies (aPLs) (triple positivity) have been identified at a high risk for thrombotic events. However, the clinical significance of isolated lupus anticoagulant (LAC) positivity is debated. Objectives: To investigate the clinical relevance of isolated LAC. Patients/Methods 456 patients were enrolled in this study; 66 antiphospholipid syndrome patients and 390 control patients. The control group existed of autoimmune patients (n=91), patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…It is widely known that LA is the aPL associated with the highest risk of thrombosis in APS patients [8,9]. In a recently published study, Yin et al analyzed 456 patients (66 APS patients vs. 390 controls) and found that isolated LA positivity was a strong predictor of vascular thrombosis (OR 7.3, CI95% 3.3-16.1), even better than triple positivity (OR 4.3, CI95% 1.6-12.2) [10]. Also, in previously published studies, LA, not triple positivity, was associated with a higher risk of thrombosis [11] and obstetric complications [12] in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely known that LA is the aPL associated with the highest risk of thrombosis in APS patients [8,9]. In a recently published study, Yin et al analyzed 456 patients (66 APS patients vs. 390 controls) and found that isolated LA positivity was a strong predictor of vascular thrombosis (OR 7.3, CI95% 3.3-16.1), even better than triple positivity (OR 4.3, CI95% 1.6-12.2) [10]. Also, in previously published studies, LA, not triple positivity, was associated with a higher risk of thrombosis [11] and obstetric complications [12] in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 CHU de Québec-Université Laval, Québec, QC, Canada. 10 Rheumatology Service, IMIBIC/Reina Sofia Hospital, University of Cordoba, Cordoba, Spain. 11 Rheumatology and Immunology Department, Peking University First Hospital, Beijing, China.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…Isolated positivity of LA, in absence of aCL and aβ2GPI, is regarded as a lower risk factor [ 4 ]. We observed that LA positivity, expressed as normalized ratio, was weaker in isolated LA-positive patients compared with LA activity in triple-positive patients, suggesting that stronger LA better corresponds with a high risk profile [ 30 ]. Attempts have been made to quantify or measure LA by other methods such as thrombin generation assays [ [31] , [32] , [33] ].…”
Section: Lupus Anticoagulantmentioning
confidence: 99%
“…Recently, a prospective observational study found that in a LA positive population the association between occurrence of thrombosis and inferior survival was independent of the detection of aCL and aβ2GPI [ 72 ]. A retrospective multicenter study illustrated that isolated LA proved to be strongly associated with vascular thrombosis even though with a weaker LA activity compared with LA activity in triple positive patients [ 30 ]. The majority of these patients was negative for aPS/PT (see also further on).…”
Section: Antibody Profilesmentioning
confidence: 99%
“…The thrombotic risk seems to be influenced by the clinical and immunological characteristics of patients with triple positive aPL patients having the highest thrombotic risk, estimated at 5.3% per year ( 11 , 12 ). However, the thrombotic potential of non-criteria aPL and the value of isolated IgM/LAC is still under investigation ( 13 15 ). Furthermore, a significant proportion of patients present a negativization of aPL during follow-up, but it is unclear if it parallels a reduction of thrombotic risk ( 16 ).…”
Section: Introductionmentioning
confidence: 99%